2009
DOI: 10.1080/02699050903283221
|View full text |Cite
|
Sign up to set email alerts
|

Early outcome in patients with traumatic brain injury, pre-injury alcohol abuse and intoxication at time of injury

Abstract: Despite a longer PTA and LOS, global and neurobehavioural outcomes at discharge from acute care were not different for those with pre-injury alcohol abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 31 publications
1
12
1
Order By: Relevance
“…These results are contrary to what have been reported in some previous investigations, 6,31 but similar to the modest paradoxical relationship reported by Vickery et al 15 and lack of relationship reported by De Guise et al 17 However, through exploratory analysis of potential interaction between our three main independent variables of interest, it was found that ethnicity and PI-ETOH interacted in predicting 6 month post-injury DRS scores. More specifically, Anglo-Caucasians and African Americans showed the predicted pattern in which PI-ETOH was associated with higher DRS scores (i.e., worse outcome).…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…These results are contrary to what have been reported in some previous investigations, 6,31 but similar to the modest paradoxical relationship reported by Vickery et al 15 and lack of relationship reported by De Guise et al 17 However, through exploratory analysis of potential interaction between our three main independent variables of interest, it was found that ethnicity and PI-ETOH interacted in predicting 6 month post-injury DRS scores. More specifically, Anglo-Caucasians and African Americans showed the predicted pattern in which PI-ETOH was associated with higher DRS scores (i.e., worse outcome).…”
Section: Discussioncontrasting
confidence: 77%
“…Some studies have shown that acute alcohol intoxication is related to increased length of hospitalization, 3,5,13 longer coma duration, 13 and lower global cognitive and functional outcome, 5,14,15 while other investigations have not shown these effects. 5-7,15,16 Likewise, studies investigating the relationship between PI-ETOH and early outcome have found that PI-ETOH was associated with lower initial Glasgow Coma Scale (GCS) scores, 15 increased length of hospitalization, 17 longer post traumatic amnesia (PTA), 17 and poorer acute global outcome, 6 although there is again conflicting evidence. 15,16,18 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[17] Limitations of the Study Hypoxia, hyperthermia and alcohol consumption were significant risk factors in other studies. [18][19][20][21][22][23] However, we did not point to these factors in our study. Although it has been shown that bradypnea had an unfavorable prognosis in TBI, considering arterial blood gases could add valuable information in analyzing respiratory function.…”
Section: Discussionmentioning
confidence: 59%